2021
DOI: 10.3390/ijms222312834
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Low and High Radiation Dose Rates on Mouse Spermatogenesis

Abstract: The adverse effects of radiation are proportional to the total dose and dose rate. We aimed to investigate the effects of radiation dose rate on different organs in mice. The mice were subjected to low dose rate (LDR, ~3.4 mGy/h) and high dose rate (HDR, ~51 Gy/h) radiation. LDR radiation caused severe tissue toxicity, as observed in the histological analysis of testis. It adversely influenced sperm production, including sperm count and motility, and induced greater sperm abnormalities. The expression of marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Furthermore, based on data revealed in recent studies, these thresholds appear to be significantly affected by the radiation dose rate. One previous study has demonstrated that LDR radiation leads to more adverse testicular damage than that following high-dose-rate (HDR) radiation, in contrast to the observed responses of other organs [21]. Research suggests that the DNA damage to spermatogonia cells and other cells during meiosis that is induced by chronic LDR irradiation may not be repaired efficiently, and the accumulating mutations may result in enhanced cell death when compared to damage induced by HDR radiation.…”
Section: Radiation-induced Impacts On Spermatogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, based on data revealed in recent studies, these thresholds appear to be significantly affected by the radiation dose rate. One previous study has demonstrated that LDR radiation leads to more adverse testicular damage than that following high-dose-rate (HDR) radiation, in contrast to the observed responses of other organs [21]. Research suggests that the DNA damage to spermatogonia cells and other cells during meiosis that is induced by chronic LDR irradiation may not be repaired efficiently, and the accumulating mutations may result in enhanced cell death when compared to damage induced by HDR radiation.…”
Section: Radiation-induced Impacts On Spermatogenesismentioning
confidence: 99%
“…Research suggests that the DNA damage to spermatogonia cells and other cells during meiosis that is induced by chronic LDR irradiation may not be repaired efficiently, and the accumulating mutations may result in enhanced cell death when compared to damage induced by HDR radiation. Nevertheless, the underlying mechanisms of this process remain to be determined [21]. This characteristic, known as the 'inverse dose-rate effect', is another important radiation-induced impact on spermatogenesis.…”
Section: Radiation-induced Impacts On Spermatogenesismentioning
confidence: 99%
“…This small mammal is common in Japan, it shows seasonal changes in seminiferous tubule morphology due to its breeding season and serves as a reference animal for the surrounding ecosystem [12,13]. Its reproductive function can be affected by physical and chemical changes as the testis is one of the most known radiosensitive organs, consisting of germ cells at different developmental stages of the spermatogenic cycle [14][15][16][17][18]. The susceptibility to radiation exposure differs between spermatogonia and spermatocytes, according to spermatogenic stages [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…At present, all factors causing decreased spermatogenesis may be the mechanism of cryptozoospermia, such as chromosomal abnormalities, 5 genetics, 6 urogenital system congenital anomalies, 7 infection, 8 immune damage, 9 testicular microlithiasis, 10 hydrocele, 11 varicocele, 12 abnormal sex hormones, 13 toxins, 14 radiation, 15 and tumors. 16 …”
Section: Introductionmentioning
confidence: 99%
“…At present, all factors causing decreased spermatogenesis may be the mechanism of cryptozoospermia, such as chromosomal abnormalities, 5 genetics, 6 urogenital system congenital anomalies, 7 infection, 8 immune damage, 9 testicular microlithiasis, 10 hydrocele, 11 varicocele, 12 abnormal sex hormones, 13 toxins, 14 radiation, 15 and tumors. 16 With the development of cryotherapy, biological treatment, drugs, surgery, assisted reproductive technology (ART), and traditional Chinese medicine (TCM), an increasing number of studies or case reports of new methods have obtained good results; however, there is no consensus, and more uncertainties need to be discussed.…”
mentioning
confidence: 99%